Human ATG2B possesses a lipid transfer activity which is accelerated by negatively charged lipids and WIPI4. (1st December 2019) - Osawa, Takuo; Ishii, Yuki; Noda, Nobuo N.
Abstract: Atg2 is one of the essential factors for autophagy. Recent advance of structural and biochemical study on yeast Atg2 proposed that Atg2 tethers the edge of the isolation membrane (IM) to the endoplasmic reticulum and mediates direct lipid transfer (LT) from ER to IM for IM expansion. In mammals, two Atg2 orthologs, ATG2A and ATG2B, participate in autophagic process. Here we showed that human ATG2B possesses the membrane tethering (MT) and LT activity that was promoted by negatively charged membranes and an Atg18 ortholog WIPI4. By contrast, negatively charged membranes reduced the yeast Atg2 activities in the absence of Atg18. These results suggest that the MT/LT activity of Atg2 is evolutionally conserved although their regulation differs among species. Abstract : Lots of phospholipids must be provided from endoplasmic reticulum for autophagosome formation. We showed that human Atg2B possesses a lipid transfer activity similarly with yeast Atg2, suggesting that Atg2 family proteins are an evolutionarily conserved lipid supplier for autophagosome formation.